DEVELOPMENT OF UZBEK POP ART DURING THE YEARS OF INDEPENDENCE - Abdukhalilov Jamshid Khurramovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the unique role of music and pop music in the years of independence of Uzbekistan, its aspects and development. It also discusses its recent past and present.